2023
DOI: 10.1021/acs.jmedchem.3c00149
|View full text |Cite
|
Sign up to set email alerts
|

2-Aminobenzoxazole Derivatives as Potent Inhibitors of the Sphingosine-1-Phosphate Transporter Spinster Homolog 2 (Spns2)

Abstract: The S1P1 receptor is the target of four marketed drugs for the treatment of multiple sclerosis and ulcerative colitis. Targeting an S1P exporter, specifically Spns2, that is “upstream” of S1P receptor engagement is an alternate strategy that might recapitulate the efficacy of S1P receptor modulators without cardiac toxicity. We recently reported the first Spns2 inhibitor SLF1081851 (16d) that has modest potency with in vivo activity. To develop more potent compounds, we initiated a structure–activity relations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 44 publications
2
10
0
Order By: Relevance
“…This substitution resulted in increased oral bioavailability as well as a nearly 50-fold increase in potency over SLF1081851 in an assay of Spns2-dependent S1P release from HeLa cells (IC 50 1.9 µM 20 vs. 0.05 µM). Like previously reported STBs 20,21 , single dose administration of SLF80821178 to mice resulted in a dose-dependent decrease in circulating lymphocytes with a maximal decrease of ∼50%. The details of the characterization of SLF80821178, a structure-activity relationship of compounds on the urea-based scaffold and their synthetic routes are the subject of a separate report (Foster, et al ., submitted for publication).…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…This substitution resulted in increased oral bioavailability as well as a nearly 50-fold increase in potency over SLF1081851 in an assay of Spns2-dependent S1P release from HeLa cells (IC 50 1.9 µM 20 vs. 0.05 µM). Like previously reported STBs 20,21 , single dose administration of SLF80821178 to mice resulted in a dose-dependent decrease in circulating lymphocytes with a maximal decrease of ∼50%. The details of the characterization of SLF80821178, a structure-activity relationship of compounds on the urea-based scaffold and their synthetic routes are the subject of a separate report (Foster, et al ., submitted for publication).…”
Section: Resultssupporting
confidence: 81%
“…For example, single doses of SLF1081851 20 , SLB1122168 21 and SLF80821178 (Foster et al ., submitted) evoke dose-dependent decreases in total blood lymphocytes in C57BL/6 mice and Sprague-Dawley rats. Further, while plasma S1P concentrations were reduced ∼15% in response to our prototype STB, SLF1081851 20 , plasma S1P concentrations were unchanged in response to SLB1122168 21 and SLF80821178 (Foster et al ., submitted) after administration of a single dose of these inhibitors. Chronic dosing of SLF80821178 in C57BL/6J mice likewise evoked lymphopenia as measured on day 15 (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Webster group also reported a new Spns2 inhibitor 33p with higher IC 50 (94 nM). 4 The IC 50 of 33p in our MS-based assay was 1.198 μM, which is slightly more potent than 16d (Supplementary information, Fig. S10d ).…”
mentioning
confidence: 89%
“…Recently, we reported a structure–activity relationship (SAR) study that identified prototypes SLF1081851 (IC 50 1.93 ± 0.04 μM) and SLF80721166 (IC 50 1.4 ± 0.3 μM) (Figure ). Additional investigations revealed a second generation Spns2 inhibitor, SLB1122168 (IC 50 94 ± 6 nM), which contained a key benzoxazole scaffold. , When administered to rodents, these inhibitors were effective in modulating the immune system as evidenced by a decrease in circulating lymphocytes, , which is a hallmark of Spns2 inhibition. In a mouse model of kidney fibrosis (unilateral ischemia-reperfusion injury), SLF1081851 suppressed inflammatory signaling in perivascular cells and ameliorated kidney fibrosis (Figure ).…”
Section: Introductionmentioning
confidence: 99%